The Use of Media Online Blogging Edmodo in Learning English Grammar - Matriwati Matriwati; Burhayani Burhayani (Universitas Muhammadiyah Prof. DR. HAMKA, 2017)
This study aims to determine the effectiveness of Edmodo media used to improve the ability of English language students especially grammar mastery. The method used in this study is the quasi experimental method with the population all of the first semester students of Basic English Structure in 2016/2017 Academic Year. The samples taken are of 2 classes (as experiment and control sample) from IC and IB class by using purposive sample technique. The total of them are 60 students.. The instruments used in this research are pre-test and posttest by following the test requirement analyses of the Chi Square normality test and homogeneity test. Then it was ssupported by the questionnaire given to the experimental class.From the normality test result for control class, both pre-test and post-test were obtained ???????? ???? = 2.89 <???????? 2 = 9.49, and ???????? ???? = 7.12 <???????? 2 = 9.49 then Ho was received and the sample of the population is normally distributed. In the pre-test of experiment class it was obtained ???????? ???? = 0.65 was smaller than ???????? 2 = 9.49, and ???????? ????= 0.71 was smaller than ???????? 2 = 9.49, so Ho was accepted and the sample of the population was also normally distribution. Based on the homogeneity test, the writer got variance of pre-test score between experiment class and control class that is Fobserved< Ftable, (1.00< 2.17), and the post test score between the experimental class and control class is Fobserved< Ftable, (1.22<2.17), hence, Ho was accepted and both data variances are homogeneous. From the calculation of independent t-test, tobserved > ttable (179 >1.67) it was found Ho was rejected and Hi hypothesis was accepted which meant that students’ mean value using Edmodo as media is higher compared with students using conventional method; without media, so it can be concluded Edmodo media can increase students’ grammar mastery in their learning.